Investigation of cerebral microbleeds in multiple sclerosis as a potential marker of blood-brain barrier dysfunction - Eisele, Philipp; Alonso, Angelika; Griebe, Martin; Szabo, Kristina; Hennerici, Michael G.; Gass, Achim (Multiple Sclerosis and Related Disorders, 2016)
Objective - In multiple sclerosis (MS) lesions blood-brain-barrier (BBB) breakdown is a common phenomenon delineating the phase of focal inflammation in developing MS lesions. In other pathologies like cerebral amyloid angiopathy or arteriosclerotic cerebral small vessel disease permanent cerebral microbleeds (CMB) have been shown to be sensitive markers indicating BBB dysfunction. We were interested in the potential role of T2*-weighted MRI and CMBs as BBB integrity markers in MS. - Methods - A large cohort of 189 MS patients (179 relapsing remitting MS and 10 secondary progressive MS) was investigated on a 3T MRI system with conventional and T2*-weighted gradient echo MRI (T2*w) sequences. T2*w images were analysed for CMBs by experienced raters. - Results - None of the MS patients showed a CMB. - Conclusion - On T2*w MRI the prevalence of CMBs is not higher in MS patients than what is to be expected in young healthy people. In contrast to pathologies with structural vascular changes like small vessel disease or cerebral amyloid angiopathy, CMBs are not seen in MS where the immune reaction is causing a functional change in the BBB.
Gesehen am 03.05.2019